One-loop corrections to the Higgs boson invisible decay in the dark doublet phase of the N2HDM - Azevedo, Duarte (2021)
The Higgs invisible decay width may soon become a powerful tool to probe extensions of the Standard Model with dark matter candidates at the Large Hadron Collider. In this work, we calculate the next-to-leading order (NLO) electroweak corrections to the 125 GeV Higgs decay width into two dark matter particles. The model is the next-to-minimal 2-Higgs-doublet model (N2HDM) in the dark doublet phase, that is, only one doublet and the singlet acquire vacuum expectation values. We show that the present measurement of the Higgs invisible branching ratio, BR(H -> invisible < 0.11), does not lead to constraints on the parameter space of the model at leading order. This is due to the very precise measurements of the Higgs couplings but could change in the near future. Furthermore, if NLO corrections are required not to be unphysically large, no limits on the parameter space can be extracted from the NLO results.